Conflict management in Indonesian football: insights from RMIFA Bandung Club - Irsan Mubarak Ismail, Muhammad; Hidayat, Dasrun; Taufik, Reza Rizkina (Faculty of Communications Science, Dr. Soetomo University, 2026)
Conflicts within football teams often arise due to performance pressure, unbalanced expectations, and communication gaps between players. This study explores how these conflicts are understood and managed in the context of Indonesian national football, utilising the perspectives of professionals at clubs based in Bandung. Based on Conflict Management Theory and Organisational Communication Theory, this study focused on three main questions: how practitioners interpret tensions between local and foreign players, how they assess the fairness and clarity of PSSI player selection practices, and which approaches they believe are most effective for strengthening team cohesion and public trust. Data were collected and obtained through semi-structured interviews with coaches, former national players, and senior football figures, using a qualitative descriptive design. The research findings highlight that consistent communication, transparent evaluation criteria, and performance-based data integration are essential to prevent conflict escalation. Clear information flow and systematic use of metrics support perceptions of fairness, while structured mediation helps restore harmony when disputes arise. This study makes a theoretical contribution by demonstrating how transparency and evidence-based decision-making strengthen organisational legitimacy and help stabilise group dynamics in professional sports teams.